On Empresses of the Latin Empire (1204–1261). Agnes of Montferrat (Maria?), the unknown daughter of Tsar Kaloyan - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2021)
The article is the second part of the series “On Empresses of the Latin Empire (1204–1261)”. This one is dedicated to Agnes of Montferrat and the second wife (probably Maria) of Emperor Henry of Flanders, and the daughter of Tsar Kaloyan. This one is dedicated to Agnes of Montferrat and the second wife (probably Maria) of Emperor Henry of Flanders, and the daughter of Tsar Koloyan. The text presents their fate and the political significance of Henry's marriages. Analyses devoted to both Henry's wives show how scarce source material is available to a historian who tries to write anything about them. The childlessness of Henry of Flanders influenced the fate of the Latin Empire. I would also like to point out that Henry went beyond the current scheme of marrying women from his own cultural circle.